DRUG UTILIZATION STUDY IN OPHTHALMOLOGY OUTPATIENT DEPARTMENT IN A GOVERNMENT TERTIARY CARE HOSPITAL IN MAHARASHTRA - Tb, Nishandar; As, Kale; Hn, Pise; Sd, Jambhrunkar (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Drug utilization research is an essential part of pharmacoepidemiology as it describes the extent, nature, and determinants of drug exposure. Indiscriminate use of topical antibiotics, steroids, and nonsteroidal anti-inflammatory drugs causes histological and structural changes in the conjunctiva. The present study was proposed to investigate prescription and drug utilization practices in ophthalmology outpatient department (OPD) in a government tertiary care hospital in Maharashtra. Methodology: An observational, cross-sectional study was conducted in a tertiary care teaching hospital of rural Maharashtra, India, from January 2015 to June 2016 after approval of the institutional ethics committee. Patients of all age group and of either gender attending ophthalmology OPD in a tertiary care hospital were included in the study. Patients not willing to consent as well as follow-up patients were excluded from the study. Data collection was done in a predesigned pro forma. Prescriptions were evaluated for demographic data, World Health Organization (WHO) core drug prescription indicators. Statistical analysis was performed using Microsoft Office ExcelÂ® 2007. Results: In a total of 600 patients, females outnumbered males. A bit less than a half of patients belonged to the age group of 19â€“45 years. An average number of drugs per encounter was (1080/600), i.e. 1.8. Of 1080 total drugs prescribed, 678 drugs (62.78%) were prescribed by their generic name. 1027/1080 (95.09%) drugs were prescribed from the National List of Essential Medicines and 671/1080 (62.13%) drugs prescribed were from the WHO- Essential medicines List. Total encounters having antibiotics and injectable formulations were 274 (45.66%) and 4 (0.66%), respectively. Discussion: Drug utilization studies (DUS) are a tool for assessing the prescribing, dispensing, and distribution of drugs. The main aim of DUS is to facilitate rational use of medicines. Overall findings of the study suggest that ophthalmologists' drug prescribing habits were appropriate to a larger extent in the current setting.